If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(-5 * 42) = 0x Multiply -5 * 42 9x(-210) = 0x Reorder the terms for easier multiplication: 9 * -210x = 0x Multiply 9 * -210 -1890x = 0x Anything times zero is zero. -1890x = 0x Solving -1890x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1890'. x = 0.0 Simplifying x = 0.0
| 3y-6x+24=0 | | 9x(-5*42)=3x | | 2x[12+9]= | | -4(b-1)+2b=3(2b-1) | | 3(s+1)-(5-2)=22s | | 7k+7k=-5(8k-6)-6(k+5) | | 5-3x+5x=-8+g+9x | | 16z-32+9=22+86 | | 16z-32+9=22-86 | | -45v+9v^2-63v^3=0 | | .01x^2-.1x-.3=0 | | -8n^5+5n^3+6n=0 | | (8n+5)(4n^2-4n-2)=0 | | 0.25*1/4^2x=1 | | x^6+i=0 | | -1/3x-2/9=-1 | | (4p+4)(2p+7)=0 | | 108x^4-46x^2-8=0 | | x^2+px+12=0 | | (3x+4x^2-6x^4)-(7x^3-3x^2+5x)=0 | | 15y=-8033+22x | | 22x+15y=8033 | | (n^3+8-3n^4)-(7n^4+1-8n^3)=0 | | x+(2x-6)=42 | | (5x^4+7x^2-8)+(4x^3+6x^4+1)=0 | | 2x+13=8x-17 | | 4m-16=-16 | | x=35+-3x | | 2(8x+y)=8y+x | | x+(3x)=35 | | x+(3*x)=35 | | 3/2x=1/3 |